Efektivitas Pelayanan Mahasiswa Pada Bagian Akademik Kantor Pusat Unsrat - Assa, Fransisca Pegiyani; Rompas, Sonny; Dengo, Salmin (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: The purpose of this research is to know the effectiveness of the Ministry on students who had been given by the officers and employees that are on the honorary academic headquarters unsrat. In the framework of the management of higher education in accordance with the Government Regulation Number 49 by 2013 about higher education, on article 11 explains that The Academic has the task of implementing the service giver education, research and community service. In the framework of the management of higher education in accordance with the Government Regulation Number 49 by 2013 about higher education, on article 11 explains that The Academic has the task of implementing the service giver education, research and community service. So in this case can be in describing how the importance of the academic section at the University of Sam Ratulangi. The research methods used in this research is qualitative, descriptive methods with gathering techniques by using the method of Observation and question form. as for the respondents/informants of this research was 5 officers, five honorary degrees, and 10 students. So a Total of 20 people was the informant. The results showed that 50% of student respondents were not satisfied with the Ministry’s officers that there is the Head Office of academic Unsrat. According to this study of student dissatisfaction because of the way delivery of employee information on students who are less friendly and does not provide information that would be expected by the student convey information, both the study also shows that 50% of students respond less well enough and with payment of tuition fee online because according to observation and research is less in case of disruption of students agree the internet is often the current payment of tuition fee can’t be done and it is very detrimental for students. The results showed that students are less agree with closing the online graduation registration 2 weeks before graduation day. Because of the internet student opinions often have disorders that does impact on the clearance delay graduation by the student file. Referring to the discussion and conclusions on top then suggest employees should be able to provide service and afford maximum to students because students are the main customers of the University of Sam Ratulangi. The friendly nature of the staff in providing service to give satisfaction in the student. Accurate information can be given to a student in any communication directly between the leadership with employees for example 1 Provost Academics should be down directly control and provide the latest information relating to the existing services in the field of academic excellence in order to provide the information needed by the student is not Academic leaders can be expected to provide services manually for the payment of the registration FEE, graduation and others in order to cope with the loss on students because in these days of frequent disruptions of the internet that could slow down the Affairs of the students ’ needs. Keywords: Service, Effectiveness